Community empowerment through increasing knowledge of the family economic in coastal communities at the Banggae Timur of Majene regency - Muhammad Yusran; Nuraeni Nuraeni; Bahrul Ulum Ilham (Indonesia Prime, 2019)
Empowerment can see as an effort to train people to have responsibilities in doing work that can improve the quality of his life. This entrepreneurship workshop is a program for community service conducted by the lecturer from the Faculty of the Economics University of West Sulawesi. This entrepreneurship Workshop is one form of empowerment training that conducted to support, create climate, atmosphere, and entrepreneurial spirit to improve the quality of life of a coastal community in District Banggae east of Majene District. Workshop activities are realized through more focused training activities, accompanied by a tutorial activity both in simulation, online practice, and learning. The purpose of this dedication is to increase the knowledge and Community affords to manage The family economy through entrepreneurship workshop activities. This Workshop can provide and provide various inputs that can unlock access to give skills to the community to have the potential of human resources that are capable as business actors or prospective business people. It characterized by increased knowledge and skill of managing business, strong encouragement to be a professional entrepreneur, seriousness to manage the financial business that based on information technology (IT) with the provision of financial management materials using accounting applications